Perancangan Katrol Sebagai Material Handling Equipment di CV. Tansa Menggunakan Quality Function Deployment - Anwar Azhar; Ilma Mufidah; Yusuf Nugroho Doyo Yekti (Jurnal Ilmiah Wahana Pendidikan, 2022)
Indonesia is famous for its cultural diversity, including culinary. Kerupuk are one of the favorite snacks in Indonesia, the large interest in consuming kerupuk in Indonesia brings a lot of jobs for the community, for example UKM Tansa Bandung which has been producing kerupuk kemplang for 30 years. Like most UKM in Indonesia, the existing infrastructure is minimal, so UKM Tansa have to move heavy goods such as semi-finished products weighing 55 kg manually by carrying them on their shoulders repeatedly every day. This becomes a problem for workers over time because it can cause health problems for workers, namely the presence of Musculoskeletal Disorders (MSDs). Problems experienced by workers can be solved by designing tools in the form of moving goods from one point to another using the Quality Function Deployment (QFD) method.